Impact of A Community Place in Regards to Sustainable Design towards Decreasing Social Crime - AFZHOOL, NADEREH (Journal of Contemporary Urban Affairs, 2019)
Human settlements have constantly provided to accommodate the wellbeing, security and the prosperity of their residents regarding plan and closeness of area to water, sustenance and other crucial assets. Safety and security have been critical issues all through history, from early ancient period to medieval and present day urban areas. In light of the populace development and quick urbanization that propels everywhere throughout the world, crime has turned out to be a standout amongst the most genuine social issues. Actually, governments and diverse specialists are attempting to vanquish this marvel by contributing a colossal measure of trade as invasive measures. Regardless, this issue is as yet uncertain as crime rates far and wide continue heightening. Dealing with and diminishing the pessimistic impacts of crime on human life will provoke more conspicuous controls and further welcome more enthusiasm of both the general population and the Community. This exploration will talk about crime and economical design concerning man and its condition with a view to decreasing the effect it has on man and nature. Designers and other design experts should mull over the encompassing condition keeping in mind the end goal to lessen. The design of structures and the game plan public offices and other outside spaces can influence the chance of crime and the level of dread of crime.